Pengembangan Instrumen Tes Untuk Mengukur Ketepatan Pukulan Ke Target Dalam Olahraga Softball: (Development of Test Instruments to Measure Accuracy Beat to The Targets in Softball Sports) - Khairurraziqin Khairurraziqin; Abdul Haris Handoko (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2020)
Softball was originally a branch of sports games played by nine players with different positions and abilities, softball in Indonesia has only been developing for several decades. This research aims to find out how the development of test instruments to measure the accuracy of punches to targets in softball sports. This research is a research and development (research and development), which means this research is a product-oriented research. The development of this test is carried out through stages: preliminary, developing, carrying out product development, product evaluation, and the final results in the form of a manual test of accuracy of punches to the target in softball sports. Data is collected through tests, questionnaires and interviews. The data is in the form of assessment results concerning product bags, suggestions for improvement, as well as other qualitative data. Quantitative data were analyzed with descriptive statistics. The suggestions obtained are used to revise the product. The results of the product quality assessment of the development of the accuracy of the hit to target test in softball are very decent with an average score of 4.7, and the average percentage score of 94%. The validity and reliability of the test obtained from the trial results is the validity of "0.448" reliability "0.697". Based on the results of the assessment, the product development test instrument to measure the accuracy of punches to the target in softball sports is feasible to be used as a test instrument to measure the accuracy of punches to the target in standard softball. Abstrak. Softball pada awalnya adalah merupakan cabang olahraga permainan yang dimainkan oleh Sembilan orang pemain dengan kedudukan dan kemampuan yang tidak sama, softball di Indonesia baru berkembang beberapa decade ini, Penelitian ini bertujuan untuk mengetahui bagaimana pengembangan instrument tes untuk mengukur ketepatan pukulan ke target dalam olahraga softball. Penelitian ini merupakan penelitian dan pengembangan (research and development), yang berarti penelitian ini merupakan penelitian yang berorientasi pada produk. Pengembangan tes ini dilakukan melalui tahapan: pendahuluan, melakukan pengembangan, melakukan pengembangan produk, evaluas iproduk, dan hasil akhir berupa buku pedoman tes ketepatan pukulan ke target dalam Olahraga softball, Data dikumpul kan melalui tes, kuesioner dan wawancara. Data berupa hasil penilaian mengenaikuali tas produk, saran untuk perbaikan, serta data kualitatif lainnya. Data kuantitatif dianalisis dengan statistic deskriptif. Saran-saran yang diperoleh digunakan untuk merevisi produk. Hasil penilaian kualitas produk pengembangan tes ketepatan pukulan ke target dalam olahraga softball ini sangat Layak dengan skor rerata 4,7, dan rerata persentase skor 94%. Validitas dan reliabiltas tes yang didapatkan dari hasil uji coba adalah validitas â€œ0,448â€ reliabilitas â€œ0,697â€, Berdasarkan hasil penilaian tersebut, produk pengembangan instrument tes untuk mengukur ketepatan pukulan ke target dalam olahraga softball ini layak digunakan sebagai instrument tes untuk mengukur ketepatan pukulan ke target dalam olahraga softball yang baku.